Metabolic profiling reveals enrichment of health-related metabolites in yoghurt by variation of strain consortium - Sandro Christensen; David Biedermann; Zahra Sattari; Thomas Roder; Mireille Tena-Stern; Carola Blaser; Pascal Fuchsmann; Ueli von Ah; Barbara Walther; Rémy Bruggmann; Stephanie C. Ganal-Vonarburg; Guy Vergères; et al. (Food Bioscience, 2025)

Biogeography and molecular diversity of coral symbionts in the genus Symbiodinium around the Arabian Peninsula - Maren Ziegler; Chatchanit Arif; John A. Burt; Sergey Dobretsov; Cornelia Roder; Todd C. LaJeunesse; Christian R. Voolstra (Journal of Biogeography, 2017)
Aim Coral reefs rely on the symbiosis between scleractinian corals and intracellular, photosynthetic dinoflagellates of the genus Symbiodinium making the assessment of symbiont diversity critical to our understanding of ecological resilience of these ecosystems. This study characterizes Symbiodinium diversity around the Arabian Peninsula, which contains some of the most thermally diverse and understudied reefs on Earth. Location Shallow water coral reefs throughout the Red Sea ( RS ), Sea of Oman ( SO ), and Persian/Arabian Gulf ( PAG ). Methods Next‐generation sequencing of the ITS 2 marker gene was used to assess Symbiodinium community composition and diversity comprising 892 samples from 46 hard and soft coral genera. Results Corals were associated with a large diversity of Symbiodinium , which usually consisted of one or two prevalent symbiont types and many types at low abundance. Symbiodinium communities were strongly structured according to geographical region and to a lesser extent by coral host identity. Overall symbiont communities were composed primarily of species from clade A and C in the RS , clade A, C, and D in the SO , and clade C and D in the PAG , representing a gradual shift from C‐ to D‐dominated coral hosts. The analysis of symbiont diversity in an Operational Taxonomic Unit (OTU)‐based framework allowed the identification of differences in symbiont taxon richness over geographical regions and host genera. Main conclusions Our study represents a comprehensive overview over biogeography and molecular diversity of Symbiodinium in the Arabian Seas, where coral reefs thrive in one of the most extreme environmental settings on the planet. As such our data will serve as a baseline for further exploration into the effects of environmental change on host–symbiont pairings and the identification and ecological significance of Symbiodinium types from regions already experiencing ‘Future Ocean’ conditions.

Erratum to: Spatial and seasonal reef calcification in corals and calcareous crusts in the central Red Sea - Anna Roik; Cornelia Roder; Till Röthig; Christian R. Voolstra (Coral Reefs, 2016)

Spatial and seasonal reef calcification in corals and calcareous crusts in the central Red Sea - Anna Roik; Cornelia Roder; Till Röthig; Christian R. Voolstra (Coral Reefs, 2016)

Metatranscriptome analysis of the reef-building coral Orbicella faveolata indicates holobiont response to coral disease - Camille A. Daniels; Sebastian Baumgarten; Lauren K. Yum; Craig T. Michell; Till Bayer; Chatchanit Arif; Cornelia Roder; Ernesto Weil; Christian R. Voolstra (Frontiers in Marine Science, 2015)

Microbiome structure of the fungid coral C tenactis echinata aligns with environmental differences - Cornelia Roder; Till Bayer; Manuel Aranda; Maren Kruse; Christian R. Voolstra (Molecular Ecology, 2015)
The significance of bacteria for eukaryotic functioning is increasingly recognized. Coral reef ecosystems critically rely on the relationship between coral hosts and their intracellular photosynthetic dinoflagellates, but the role of the associated bacteria remains largely theoretical. Here, we set out to relate coral‐associated bacterial communities of the fungid host species C tenactis echinata to environmental settings (geographic location, substrate cover, summer/winter, nutrient and suspended matter concentrations) and coral host abundance. We show that bacterial diversity of C . echinata aligns with ecological differences between sites and that coral colonies sampled at the species’ preferred habitats are primarily structured by one bacterial taxon (genus Endozoicomonas ) representing more than 60% of all bacteria. In contrast, host microbiomes from lower populated coral habitats are less structured and more diverse. Our study demonstrates that the content and structure of the coral microbiome aligns with environmental differences and denotes habitat adequacy. Availability of a range of coral host habitats might be important for the conservation of distinct microbiome structures and diversity.

Mesophotic coral depth acclimatization is a function of host-specific symbiont physiology - Maren Ziegler; Cornelia M. Roder; Claudia Büchel; Christian R. Voolstra (Frontiers in Marine Science, 2015)

Limits to physiological plasticity of the coral Pocillopora verrucosa from the central Red Sea - Maren Ziegler; Cornelia M. Roder; Claudia Büchel; Christian R. Voolstra (Coral Reefs, 2014)

Bacterial profiling of W hite P lague Disease across corals and oceans indicates a conserved and distinct disease microbiome - Cornelia Roder; Chatchanit Arif; Camille Daniels; Ernesto Weil; Christian R. Voolstra (Molecular Ecology, 2014)
Coral diseases are characterized by microbial community shifts in coral mucus and tissue, but causes and consequences of these changes are vaguely understood due to the complexity and dynamics of coral‐associated bacteria. We used 16S rRNA gene microarrays to assay differences in bacterial assemblages of healthy and diseased colonies displaying White Plague Disease (WPD) signs from two closely related Caribbean coral species, Orbicella faveolata and Orbicella franksi . Analysis of differentially abundant operational taxonomic units (OTUs) revealed strong differences between healthy and diseased specimens, but not between coral species. A subsequent comparison to data from two Indo‐Pacific coral species ( Pavona duerdeni and Porites lutea ) revealed distinct microbial community patterns associated with ocean basin, coral species and health state. Coral species were clearly separated by site, but also, the relatedness of the underlying bacterial community structures resembled the phylogenetic relationship of the coral hosts. In diseased samples, bacterial richness increased and putatively opportunistic bacteria were consistently more abundant highlighting the role of opportunistic conditions in structuring microbial community patterns during disease. Our comparative analysis shows that it is possible to derive conserved bacterial footprints of diseased coral holobionts that might help in identifying key bacterial species related to the underlying etiopathology. Furthermore, our data demonstrate that similar‐appearing disease phenotypes produce microbial community patterns that are consistent over coral species and oceans, irrespective of the putative underlying pathogen. Consequently, profiling coral diseases by microbial community structure over multiple coral species might allow the development of a comparative disease framework that can inform on cause and relatedness of coral diseases.